Stewart-Treves syndrome: a rare entity - Dhillon, K. S.; Sharma, Deepak; Fatima, Uroos; Singh, Isha; Garg, Nikha; Singh, Tarunveer; Gupta, Tanu; Khan, Nawed (International Journal of Advances in Medicine, 2017)
Stewart-Treves syndrome is a rare, deadly cutaneous angiosarcoma that develops in long - standing chronic lymphedema. Most commonly, this tumor is a result of lymphedema induced by radical mastectomy to treat breast cancer. Stewart-Treves syndrome occurs in 0.5% of patients, who survive mastectomy for more than 5 years. The mean age at appearance of the angiosarcoma is 62 years, and the mean interval between mastectomy and the appearance of the tumor is 10.5 years. The exact pathogenesis is not known so far. On histopathology, vascular channels infiltrate the normal structures in a disorganized fashion, as if trying to line every available tissue space with a layer of endothelial cells. The prognosis is poor as it is very aggressive. Only early diagnosis and prompt radical excision with or without adjuvant radiotherapy, can promote survival.